Benzimidazole‐based fluorophores for the detection of amyloid fibrils with higher sensitivity than Thioflavin‐T. Issue 6 (9th September 2020) - Pravin, Narayanaperumal; Kumar, Rakesh; Tripathi, Shalini; Kumar, Pardeep; Mohite, Ganesh M; Navalkar, Ambuja; Panigrahi, Rajlaxmi; Singh, Namrata; Gadhe, Laxmikant G.; Manchanda, Shaffi; Shimozawa, Makoto; Nilsson, Per; et al.
Abstract: Protein aggregation into amyloid fibrils is a key feature of a multitude of neurodegenerative diseases such as Alzheimer's, Parkinson's, and Prion disease. To detect amyloid fibrils, fluorophores with high sensitivity and better efficiency coupled with the low toxicity are in high demand even to date. In this pursuit, we have unveiled two benzimidazole‐based fluorescence sensors ([C15 H15 N3 ] (C1 ) and [C16 H16 N3 O2 ] (C2 ), which possess exceptional affinity toward different amyloid fibrils in its submicromolar concentration (8 × 10 –9 M), whereas under a similar concentration, the gold standard Thioflavin‐T (ThT) fails to bind with amyloid fibrils. These fluorescent markers bind to α‐Syn amyloid fibrils as well as amyloid fibrils forming other proteins/peptides including Aβ42 amyloid fibrils. The 1 H‐ 15 N heteronuclear quantum correlation spectroscopy nuclear magnetic resonance data collected on wild‐type α‐Syn monomer with and without the fluorophores (C1 and C2 ) reveal that there is weak or no interactions between C1 or C2 with residues in α‐Syn monomer, which indirectly reflects the specific binding ability of C1 and C2 to the α‐Syn amyloid fibrils. Detailed studies further suggest that C1 and C2 can detect/bind with the α‐Syn amyloid fibril as low as 100 × 10 –9 M. Extremely low or no cytotoxicity is observed for C1 and C2 and they do not interfere with α‐Syn fibrillation kinetics, unlike ThT. Both C1 /C2 not only shows selective binding with amyloid fibrils forming various proteins/peptides but also displays excellent affinity and selectivity toward α‐Syn amyloid aggregates in SH‐SY5Y cells and Aβ42 amyloid plaques in animal brain tissues. Overall, our data show that the developed dyes could be used for the detection of amyloid fibrils including α‐Syn and Aβ42 amyloids with higher sensitivity as compared to currently used ThT. Abstract : A new generation of benzimidazole‐based fluorophores ([C15 H15 N3 ] (C1 ) and [C16 H16 N3 O2 ] (C2 )) outperforms standard marker Thioflavin‐T (ThT) in detecting α‐synuclein (α‐Syn) amyloid fibril in their submicromolar concentration. The stability of the complexes (C1‐α‐Syn amyloid fibril or C2‐α‐Syn amyloid fibril) formed by these fluorophores is three orders of magnitude larger than the adduct formed by ThT. Unlike ThT, C1, and C2 do not induce/interfere with aggregation kinetics and it could detect α‐Syn fibril as low as 100 nM concentration. These fluorophores also bind to Aβ plaques in animal tissue.